Assessment of the Attractiveness of Sacred Tourism - D. Ussubaliyeva, Saltanat; Uaisova, Amina; D. Aitbayeva, Gulzamira; Kh. Zhubanova, Mariyash; Bessekey, Yerkin (International Journal of Criminology and Sociology, 2022)
The article presents the experience of scoring sacred objects, the most promising for the purposes of development of sacred tourism in the territory of Almaty region of Kazakhstan. These objects were the object of research, and the subject was the methodology of integrated assessment of these objects in order to determine the most priority and promising centers of sacred tourism in the studied territory. The research purpose is to determine the tourist attractiveness of sacred objects of Almaty region. The level of tourist attractiveness of sacred objects of Almaty region was assessed using the method of expert assessments. The tourist attractiveness of the studied objects was estimated in points by 3 groups (suitability, accessibility, significance) and by 6 indicators. 14 most attractive sacred objects for tourists of Almaty region were allocated. The obtained results allow the parties interested in the development of sacred tourism to concentrate their efforts on developing the most attractive sacred objects for tourists.